The Role of Protein Kinase mTOR in Th2 Polarization of the Immune Response in Bronchial Asthma in Сhildren - O.P. Volosovets; S.P. Kryvopustov; O.V. Pavlyk (Zaslavsky O.Yu., 2015)
Objective of this study was to determine whether single-nucleotide polymorphism (SNP) in mTOR gene is associated with development of allergic phenotype in children. Methods. Genotyping for mTOR (rs11121704) was performed in the following populations: patients with asthma (n = 91; ages 5-18 years), and control group (n = 87; ages 5-18 years) using real-time polymerase chain reaction. Results. We have found that 50 (54.9 %) of patients from the study group and 43 (49.4 %) subjects from the control group had major allele of rs11121704 in mTOR, 36 (39.6 %) and 32 (36.8 %), respectively, - heterozygous allele, and 5 (5.5 %) and 12 (13.8 %) - minor allele. Variants of rs11121704 minor genotype in the gene mTOR were 2.5 times more likely in the control group than among patients of the study group. Conclusions. We supposed that SNP in mTOR may independently serve as perspective marker to predict the development of asthma and other allergic diseases among children.